Medication reconciliation in a medical clinic unit as a strategy for Patient Safety in a university hospital (Research, Society and Development, 2022)
Introduction: Patient Safety has become a priority in health services, a continuous process involving educational activities and systematic actions aimed at reducing risk situations to the patient. Medication conciliation stands out among the main tools to prevent medication errors in patient care transition. Objective: To analyze the profile of medication reconciliation in patients admitted to a university hospital. Methodology: This is a descriptive and prospective study in the medical clinic unit of the university hospital located in the State of Amazonas in the semester of 2020. Results: A total of 237 visits were performed, of which 180 patients met the study inclusion criteria. There was a predominance of females, and the mean age was 46.67± 17.58 years, and the patients were mostly aged between 41 and 70 years. Among the discrepancies identified, about 56% were intentional and 44% unintentional. In unintentional discrepancies, we detected 50% due to omission of the medication, 25% from incorrect dose, and 25% from incorrect dosage. Regarding pharmaceutical interventions in unintentional discrepancies, 75% were accepted by the medical team. Conclusion: The performance of the medication reconciliation service by the clinical pharmacy team is of great importance for patient safety in the hospital environment, being a fundamental instrument for optimizing pharmacotherapy.